PENINGKATAN MOTIVASI DAN HASIL BELAJAR IPA MENGGUNAKAN MODEL PEMBELAJARAN RECIPROCAL TEACHING PADA SISWA SEKOLAH DASAR - Mega Wati (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2021)
This research is motivated by the problem of low motivation and science learning outcomes for fifth grade students at 094/8 Giriwinangun.. This is because teachers still teach conventionally and do not apply variations in teaching. The purpose of this study is to increase motivation and science learning outcomes using the reciprocal teaching learning model for fifth grade students. This research is a type of CAR research, which has been carried out in two cycles of action, while each cycle consists of two meetings. Each cycle consists of planning, implementation of action, observation, and reflection. Data collection techniques in this study used observation, questionnaires, and learning outcomes tests. The observation sheet instrument was used to collect data related to the teacher and student aspects of the learning process, the questionnaire instrument was used to collect data related to student learning motivation, while the learning outcomes test items were used to collect data related to the remaining science learning outcomes. The research data were analyzed using qualitative and quantitative approaches. The results showed that in the first cycle the learning process in the teaching aspect of the teacher reached 75%, the student learning aspect reached 65%. In the second cycle the improvement in the learning process from the teaching aspect of the teacher reached 87%, student learning aspect in the second cycle reached 90%. The success percentage of students' learning motivation in the first cycle reached 70% and increased again in the second cycle by reaching 95%. Students' science learning outcomes in the first cycle only reached classical completeness of 55%. While in the second cycle, it managed to increase by achieving classical completeness of 80%. Based on the results of the study, it can be concluded that the application of the reciprocal teaching model can increase the motivation and learning outcomes of science students in class V SDN 094/8 Giriwinangun.